Manajemen Pelayanan Bimbingan Konseling - A'an Yusuf Khunaifi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2020)
This research aims to determine the management of counseling services in MAN 4 Kediri including planning, organizing, implementing, and supervision. This method of research is a qualitative descriptive of phenomenology in the application of management guidance and counseling services. The results of the study showed the planning of counseling guidance program based on the results of student and environmental needs analysis, organizing officers conducted counseling guidance coordinator based on the agreement between teachers and Counseling. Implementation of activities refers to the unit of service activity: 1) Orientation service is the introduction of new students to the school order and the character of each teacher of study field; 2) Individual counseling services The teachers try to open counseling for the problematic students to devote their hearts to the counseling teachers; 3) Group counseling Services i.e. teacher Counseling Tutoring creates personal and group accounts on social media Facebook; 4) Mediation services in conducting problematic student mediation, counseling teachers collaborate with the class and parents to overcome a problematic student. Here teachers counseling guidance tries to mediate by calling the students and their parents to resolve the problem; 5) Supporting activities: a) home visits; b) instead of a case. In addition to that also in the implementation of counseling guidance services There is equipment that supports the governance of counseling guidance. Like the case book for students who are stuck in problems such as smoking is discovered in the middle of the school, caught fouling and others. Outside school counseling teachers also conduct observations at the student's home through visits and observations to obtain detailed student information.